Bilingual Skills in Learning for Islamic Education Students in the International Special Class Program (KKI) at Sultan Aji Muhammad Idris State Islamic University Samarinda - Marroh, Zahrotul Istianah; Pimada, Luluk Humairo; Achmad, Andi (Poltanesa, 2024)
This research departs from the importance of foreign language skills as one of the efforts to improve the competencies that must be possessed by every teacher or prospective Islamic Religious Education teacher. Therefore, in improving these competencies, a program is needed that is designed to form language skills for Islamic Education students who will become Islamic Education Teachers in the future. To support this program, the International Special Class at Sultan Aji Muhammad Idris State Islamic University Samarinda   has developed a curriculum to support the advancement of students' foreign language skills in both English and Arabic. International special class management is needed in harmonizing the international special class curriculum (KKI) with concepts and activities related to language both English and Arabic in daily life in the classroom. The KKI program is expected to be able to compete with international universities as well with the provision of foreign language during their special class program. The Arabic language proficiency formation program for PAI students in the International Special Class Program (KKI) uses two programs TOAFL and Muhadharah. The English language proficiency formation program for PAI students in the International Special Class Program (KKI) has two language proficiency formation programs TOEFL and Public Speaking. This program is certainly supported by lecturers who speak English and Arabic to support this learning. It is hoped that alumni of the international special class (KKI) at Sultan Aji Muhammad Idris State Islamic University Samarinda   can improve human resources and services to the community.